Chitosan-collagen biomembrane embedded with calcium-aluminate enhances dentinogenic potential of pulp cells - Diana Gabriela SOARES; Hebert Luís ROSSETO; Fernanda Gonçalves BASSO; Débora Salles SCHEFFEL; Josimeri HEBLING; Carlos Alberto de Souza COSTA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The development of biomaterials capable of driving dental pulp stem cell differentiation into odontoblast-like cells able to secrete reparative dentin is the goal of current conservative dentistry. In the present investigation, a biomembrane (BM) composed of a chitosan/collagen matrix embedded with calcium-aluminate microparticles was tested. The BM was produced by mixing collagen gel with a chitosan solution (2:1), and then adding bioactive calcium-aluminate cement as the mineral phase. An inert material (polystyrene) was used as the negative control. Human dental pulp cells were seeded onto the surface of certain materials, and the cytocompatibility was evaluated by cell proliferation and cell morphology, assessed after 1, 7, 14 and 28 days in culture. The odontoblastic differentiation was evaluated by measuring alkaline phosphatase (ALP) activity, total protein production, gene expression of DMP-1/DSPP and mineralized nodule deposition. The pulp cells were able to attach onto the BM surface and spread, displaying a faster proliferative rate at initial periods than that of the control cells. The BM also acted on the cells to induce more intense ALP activity, protein production at 14 days, and higher gene expression of DSPP and DMP-1 at 28 days, leading to the deposition of about five times more mineralized matrix than the cells in the control group. Therefore, the experimental biomembrane induced the differentiation of pulp cells into odontoblast-like cells featuring a highly secretory phenotype. This innovative bioactive material can drive other protocols for dental pulp exposure treatment by inducing the regeneration of dentin tissue mediated by resident cells.